1974
DOI: 10.3758/bf03197488
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of prenominal adjective orders

Abstract: In two experiments, phrases describing a referent object contained two prenominal adjectives in either normal or inverted order. The time to identify the position of the referent in a display was a function of both the adjective order and the nonreferent context. If the referent appeared with a nonreferent differing from it only in size or number. the normal order of adjectives facilitated responding. However, if the referent appeared with a nonreferent differing from it only in color, the inverted order of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In several studies, it has been argued that AO is solely "determined by the pragmatic demands of the communication situation" (Danks & Glucksberg 1971: 66;cf. also Danks & Schwenk 1972, 1974, i.e. by a pragmatic communication rule which states that adjectives are primarily ordered according to the adjectives' discriminative potential: more discriminating adjectives precede less discriminating ones.…”
Section: Normal Vs Contextually Constrained Adjective Ordermentioning
confidence: 99%
“…In several studies, it has been argued that AO is solely "determined by the pragmatic demands of the communication situation" (Danks & Glucksberg 1971: 66;cf. also Danks & Schwenk 1972, 1974, i.e. by a pragmatic communication rule which states that adjectives are primarily ordered according to the adjectives' discriminative potential: more discriminating adjectives precede less discriminating ones.…”
Section: Normal Vs Contextually Constrained Adjective Ordermentioning
confidence: 99%
“…One could argue that the learning observed in the current study is not simply ‘stylistic’ because it is possible that – in real-life referential communication – differences in adjective ordering entail different meanings (Danks & Glucksberg, 1971; Danks & Schwenk, 1972, 1974; Scontras, 2023; Whorf, 1945). As discussed in the introduction section, this is unlikely in the context of the current study.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the weak adjective ordering preferences in Hebrew could allow us to examine stylistic non-crucial meaning preferences. Some research on English suggests that adjective ordering variation is linked to meaning inference (Danks & Glucksberg, 1971;Danks & Schwenk, 1972, 1974Scontras, 2023;Whorf, 1945). Specifically, it has been shown that deviation from the common adjective order in English, by placing a certain adjective earlier in the sequence than it usually is, could implicate that some feature of the object is especially worth emphasizing (Martin, 1970;Martin & Ferb, 1973).…”
Section: The Current Studymentioning
confidence: 99%